2019
DOI: 10.2807/1560-7917.es.2019.24.41.1800594
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors and genetic characterisation of extended-spectrum beta-lactamase and carbapenemase-producing Enterobacteriaceae (ESBL-E and CPE): a community-based cross-sectional study, the Netherlands, 2014 to 2016

Abstract: BackgroundThe epidemiology of carriage of extended-spectrum beta-lactamase-producing (ESBL-E) and carbapenemase-producing Enterobacteriaceae (CPE) in the general population is unknown.AimIn this observational study, the prevalence and risk factors for intestinal ESBL-E and CPE carriage in the Dutch general population were determined. ESBL-E were characterised.MethodsFrom 2014 to 2016, ca 2,000 residents were invited monthly to complete a questionnaire and provide a faecal sample, which was tested for ESBL-E. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
63
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(85 citation statements)
references
References 36 publications
(49 reference statements)
14
63
4
1
Order By: Relevance
“…However, a Dutch study conducted in 2014-2016 used similar methods as the current study and they found that 10.6% of the 555 dogs carried ESBL-E [4]. In addition, they also reported that 3.8% of the owners were carriers, which was slightly lower than the 4.5% prevalence rate reported from the Dutch general population [4,14]. The carriage rate in Dutch citizens is comparable to 4.7% reported from Sweden in 2013 [15], so it is interesting to note the large difference between carriage rates in Dutch and Swedish dogs.…”
Section: Resultssupporting
confidence: 62%
“…However, a Dutch study conducted in 2014-2016 used similar methods as the current study and they found that 10.6% of the 555 dogs carried ESBL-E [4]. In addition, they also reported that 3.8% of the owners were carriers, which was slightly lower than the 4.5% prevalence rate reported from the Dutch general population [4,14]. The carriage rate in Dutch citizens is comparable to 4.7% reported from Sweden in 2013 [15], so it is interesting to note the large difference between carriage rates in Dutch and Swedish dogs.…”
Section: Resultssupporting
confidence: 62%
“…Besides human-to-human transmission, potential routes of transmission of ESBL-E to humans are the food chain, direct contact with animals or indirectly via the environment [3]. The prevalence of the faecal carriage of ESBL-E in the general population in the Netherlands is approximately 5% [46].…”
Section: Text Short Reportmentioning
confidence: 99%
“…From 2014 to 2017, the faecal carriage of ESBL-producing E. coli and K. pneumoniae was determined in three different large cross-sectional studies in the Netherlands in the selections of predominantly healthy individuals in the population at large: the Livestock Farming and Neighbouring Residents' Health Study (VGO) [5], the ESBL-population study (ESBLAT) [6] and a study on ESBL-producing bacteria among vegetarians and non-vegetarians (Vega Study) [16]. The VGO study was performed from February 2012 to May 2014 among the general population aged 18–70 years old living in a livestock-dense area in the south of the Netherlands, and after consent to participate in further studies, ESBL-E/K faecal carriage was assessed between February 2014 and May 2015 [5].…”
Section: Text Short Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…One interpretation of this correlation is that the dissemination of resistance is favoured by poor sanitation. More convincingly, the individual carriage of extended-spectrum beta-lactamase-producing E. coli (an enzyme conferring resistance to beta-lactams antibiotics) was strongly associated with an indicator of poor hygiene in a large cohort [46]. However, it is not at all obvious in theory why transmission would favour resistance.…”
Section: The Role Of Transmission and Supercolonization On Mdrmentioning
confidence: 99%